A Survey on the use of Social BPM in Practice in Brazilian Organizations - Batista, Matheus; Magdaleno, Andréa; Kalinowski, Marcos (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2017: Anais do XIII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2017.6073, 2017)
Social BPM is the combination of Business Process Management (BPM) with social and collaborative techniques for the purpose of exploring collaboration among stakeholders throughout the BPM lifecycle. Its goals are to reduce common problems in BPM by ensuring collaboration and transparency. To the best of our knowledge, there is no information on how Social BPM is being used in organizational environments and on its impacts. This study aims at showing how Brazilian organizations are using Social BPM practices and technologies. Therefore, a survey was conducted with employees from different companies in order to collect data on their usage of BPM collaborative practices. The survey received 31 replies and 3 of the respondents were also interviewed in order to provide depth to their answers and to enhance the overall understanding. The results show that collaboration happens predominantly in design, modeling, and improvement phases. Collaboration still happens mainly without formal planning and without tool support.